TWO ORDINARY HYPERGEOMETRIC DEFINITE INTEGRALS INVOLVING RAMANUJANaS FORMULA (Global Journal of Science Frontier Research, 2011)
The aim of this paper is to develop certain ordinary definite integrals in association with Ramanujan's formula .
Keywords: Generalized Gaussian hypergeometric function; Fox H-function